2003
DOI: 10.1023/a:1022676709565
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: AFM is demonstrated to be a valuable tool in visualization and quantification of drug nanoparticle crystals in formulations. In addition to accurate size measurement, AFM readily provides shape and structural information of nanoparticles, which cannot be obtained by light scattering. Ultramicrotomy is a good sample preparation method to expose the interior of solid dosage forms with minimal structural alteration for microscopic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 7 publications
1
10
0
2
Order By: Relevance
“…AFM is widely used for studying of thin polymer and oligopeptides films, drugs and other crystalline compounds to determine the size and shape of crystallites. [ 30 31 32 33 ] Results obtained in the present work are in agreement with the earlier results for different PEGs which showed a low roughness of the surface of the films of this polymer. [ 34 35 ] Low roughness indicates a smoothness of the individual polymer film which allows determining the presence and sizes of crystallites and nanoparticles in the PEG-1000 film.…”
Section: Discussionsupporting
confidence: 92%
“…AFM is widely used for studying of thin polymer and oligopeptides films, drugs and other crystalline compounds to determine the size and shape of crystallites. [ 30 31 32 33 ] Results obtained in the present work are in agreement with the earlier results for different PEGs which showed a low roughness of the surface of the films of this polymer. [ 34 35 ] Low roughness indicates a smoothness of the individual polymer film which allows determining the presence and sizes of crystallites and nanoparticles in the PEG-1000 film.…”
Section: Discussionsupporting
confidence: 92%
“…4,5) Shi et al reported the image of drug nanocrystals in the formulation by atomic force microscopy and complementary techniques. 8) They showed the morphology of nanocrystals, though the surface states of the nanocrystals were not well characterized.…”
mentioning
confidence: 99%
“…The non-conducting samples like polymeric nano-materials, micro-crystals, etc. can be easily characterized by this approach that is the main advantage of this technique [57].…”
Section: Characterization Approach/ Techno-
Logies For Nanosuspensionmentioning
confidence: 99%